Endoscopic Vacuum Therapy: A Boon for the Patients with Post-surgical Anastomotic Site Leaks - Kale, Aditya; Thakur, Sukanya; Jearth, Vaneet (Journal of Digestive Endoscopy, 2025)
Postoperative leaks remain a significant clinical problem with high morbidity and mortality. Traditionally, image-guided pigtail drain placement for collections, feeding tube placement for nutrition, clips or clip–loop combinations for defect closure, surgical repair with buttressing, excision of esophageal conduit and colonic interposition for esophageal leaks, colostomy, and revision of anastomosis for colorectal leaks are often employed. Recently, endoscopic vacuum therapy has gained popularity due to being a minimally invasive, safe, and effective therapeutic option. In this news and views, we will review studies and literature related to this topic.
Keywords: leaks; endoscopic vacuum therapy; complications; perforation